On the determination of spectral optical characteristics of the earth atmosphere - G, Batsukh; D, Gangbaatar; D, Khaltar; B, Jargal; Ts, Baatarchuluun; D, Ochirbat (Scientific transaction of the National University of Mongolia. Physics, 2022)
Spectral optical characteristics of the earth atmosphere are used and can be used for the physical state analysis of the atmosphere and right accounting of radiation extinction in carring out of environmental remote sensing, determination of the composition and properties of aerosols and solar energy absolute spectrophotometric measurements as well as for the selection of the optimum conditions of solar energetic installations work and an evaluation of the atmosphere pollution in the different regions of the globe.